A Study of the Incidence of Fifth Pair of Sacral Foramina - Dr. B.R.Ramesh, Dr. Balachandra N., Dr. Poonam D N. (International Journal of Innovative Research in Medical Science, 2017)
Low backache is a common condition affecting majority of the population. One of the causes is sacralization of lumbar vertebra. These are called lumbosacral transitional abnormalities which occur as a result of congenital anomaly in the segmentation of the lumbosacral spine. It includes either the involvement of L5 in sacrum or S1 into the lumbar vertebraeBertolotti 1st observed the LSTV and stated that these abnormal vertebrae may produce low back pain due to arthritic changes which occur at the site of false articulation. LSTV are common with the prevelance ranging from 1-20%. Context and purpose of the study: Lumbosacral transitional vertebrae occur as a congenital anomaly in the segmentation of the lumbosacral spine. Some previous workers have suggested the role of LSTV in low back pain, whereas others have contradicted the role of LSTV. This study helps clinicians to rule out LSTV/ Sacralization while diagnosing a case of low back pain. Presence of 5 pairs of ventral and dorsal sacral foramina has been observed. Such an increase in the number of foramina has been noticed quite frequently, hence the present study Results: Additional sacral foramina were found in 07 sacra Clinical implications: Sacralization is not related to low backache, it can remain asymptomatic for many years, however sometimes, it gives rise to pain which begins slowly and gradually gets worse which may be due to - actual pressure on nerve / nerve trunks; ligamentous strain; compression of soft tissues between bony joints; by an actual arthritis if a joint is present; by bursitis if a bursa if present. There is no difference between the two sexes in the prevalence of sacralization contradicting previous claims that neither is more common in females nor was spondylolisthesis found more frequently in men. Investigations to diagnose such condition in clinical practice are plain x-rays, CT scan, and MRI.